A preliminary study of medial temporal lobe function in youths with a history of caregiver deprivation and emotional neglect. - Maheu, F; Dozier, M; Guyer, A; Mandell, D; Peloso, E; Poeth, K; Jenness, J; Lau, J; Ackerman, J; Pine, D; Ernst, M (2010)
Previous research findings have linked caregiver deprivation and emotional neglect with sensitivity to threatening cues. The present preliminary study investigated whether dysfunctions of the medial temporal lobe could underlie these associations. Using fMRI, we measured medial temporal lobe responses to emotional faces (angry, fearful, happy, neutral) among 30 youths. Eleven of the youths had a history of caregiver deprivation and emotional neglect. Attention states (i.e., attention to anger, fear, or physical attributes, or passive viewing) were systematically manipulated. Relative to comparison youths, youths with a history of caregiver deprivation and emotional neglect showed significantly greater left amygdala and left anterior hippocampus activation during the processing of threatening information. To our knowledge, these findings are the first to demonstrate altered medial temporal lobe function during the processing of threat cues in youths with a history of caregiver deprivation and emotional neglect.